Multiscale gigapixel photography - Brady, D. J.; Gehm, M. E.; Stack, R. A.; Marks, D. L.; Kittle, D. S.; Golish, D. R.; Vera, E. M.; Feller, S. D. (Nature (London), 2012)
The AWARE-2 camera uses a parallel array of microcameras to capture one-gigapixel images at three frames per minute. Very candid camera Current digital cameras operate around megapixels. Broadly speaking, the higher the pixel count, the more enlargement an image can take. But when gigapixel 'supercameras' become readily available, photography will undergo a second digital revolution. The current emphasis on visual image capture will be a thing of the past. Gigapixel cameras will generate massive data sets, so the emphasis will be on post-capture analysis and data-mining. It is already possible to achieve an arbitrarily large pixel count using massed arrays of cameras, but at a high cost and with extreme complexity. These authors have developed a compact gigapixel camera capable of taking gigapixel images at three frames per minute. The system is based on a 'multiscale' optical system and a specially designed electronic processing unit to process the large volume of imaging information at high speed. They demonstrate with imaging examples that a wealth of information can be obtained from gigapixel snapshots. Pixel count is the ratio of the solid angle within a camera’s field of view to the solid angle covered by a single detector element. Because the size of the smallest resolvable pixel is proportional to aperture diameter and the maximum field of view is scale independent, the diffraction-limited pixel count is proportional to aperture area. At present, digital cameras operate near the fundamental limit of 1–10 megapixels for millimetre-scale apertures, but few approach the corresponding limits of 1–100 gigapixels for centimetre-scale apertures. Barriers to high-pixel-count imaging include scale-dependent geometric aberrations, the cost and complexity of gigapixel sensor arrays, and the computational and communications challenge of gigapixel image management. Here we describe the AWARE-2 camera, which uses a 16-mm entrance aperture to capture snapshot, one-gigapixel images at three frames per minute. AWARE-2 uses a parallel array of microcameras to reduce the problems of gigapixel imaging to those of megapixel imaging, which are more tractable. In cameras of conventional design, lens speed and field of view decrease as lens scale increases 1 , but with the experimental system described here we confirm previous theoretical results 2 , 3 , 4 , 5 , 6 suggesting that lens speed and field of view can be scale independent in microcamera-based imagers resolving up to 50 gigapixels. Ubiquitous gigapixel cameras may transform the central challenge of photography from the question of where to point the camera to that of how to mine the data.